Morphology and Evolution of Slopes in the Upper Luni Basin, Rajasthan - Kar, Amala (Annals of Arid Zone, 2016)
Studies on the morphology of slopes and slope-forming factors in the Upper Luni Basin have indicated that the climatic gradation from east to west has greatly influenced the broad changes in slope pattern in that direction. Thus, while in the east there is more of convexo-concave regolith-covered slopes, the western part has more of faceted, debris-free and slightly concave slopes. Moreover, the Incidence of valley slope does also decrease towards the west. Complexities within this general pattern are, however, provided by the rock characteristics and structural features like fault lines. Within the Aravallis slope decline is most dominant, while in the desert plains slope retreat and slope replacement are common.